PENGARUH UKURAN PERUSAHAAN DAN POTENSI KESULITAN KEUANGAN PADA KONSERVATISME AKUNTANSI DENGAN LEVERAGE SEBAGAI PEMODERASI - Tista, Kadek Weda Noveadjani; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
The financial statements is management tool to provide information about management’s accountability in managing a company which is used as basis for a decision making by the the financial statement users guided by Generally Accepted Accounting Principles (GAAP). It enables management to have the opportunity to apply conservatism in the financial statements. A total of 98 observation samples to 34 companies listed on the Stock Exchange in 2011-2015 selected by non-probability sampling method especially purposive sampling technique. Moderated regression analysis was used as analytical techniques and the results are the size of the company's has negative effect on accounting conservatism otherwise potential of financial distress has a positive effect on the company's financial accounting conservatism. Leverage can amplify the effect of firm size on accounting conservatism, but are not able to moderate the influence of the potential financial difficulties in accounting conservatism.
Keywords: company size, the potential financial distress, leverage, accounting conservatism